Delaying urinary catheter insertion in the reception and resuscitation of blunt multitrauma and using a full bladder to tamponade pelvic bleeding. Issue 6 (June 2015) - Huang, Sean; Vohora, Ashray; Russ, Matthias K.; Mathew, Joseph K.; Johnny, Cecil S.; Stevens, Jeremy; Fitzgerald, Mark C.
Abstract This article proposes a counter-argument to standard Advanced Trauma Life Support (ATLS) training – which advocates bladder catheterisation to be performed as an adjunct to the primary survey and resuscitation for early decompression of the bladder and urine output monitoring. We argue the case for delaying bladder catheterisation until after definitive truncal Computed Tomography (CT) imaging. To reduce pelvic volume and associated bleeding, our trauma team delay catheter insertion until after the initial CT scan. The benefits of a full bladder also include improved views on initial Focussed Assessment with Sonography in Trauma (FAST) scan and improved interpretation of injuries on CT. Our urinary catheter related infection rates anecdotally decreased when insertion was delayed and consequently performed in a more controlled, non-resuscitation setting following CT. Adult blunt multitrauma patients with pelvic ring fractures are at risk of significant haemorrhage. Venous, arterial and medullary injuries with associated bleeding may be potentiated by an increased pelvic volume with ring disruption, as well as a reduced pressure effect from retroperitoneal and intra-pelvic organs on bleeding sites. Various techniques are used to reduce intra-pelvic bleeding. For shocked patients who have sustained major pelvic injuries with no other signs of urinary tract trauma and minimal urine in the bladder on initial FAST scan, we advocate careful, aseptic Foley catheter insertion followed by bladder insufflation with 500–600 mL of Normal Saline (NS) and subsequent catheter clamping to tamponade pelvic bleeding.